Current landscape of exosomes in tuberculosis development, diagnosis, and treatment applications - Sun, Xuezhi; Li, Wei; Zhao, Li; Fan, Ke; Qin, Fenfen; Shi, Liwen; Gao, Feng; Zheng, Chunlan (Frontiers in Immunology, 2024)
Tuberculosis (TB), caused by the bacterial pathogen Mycobacterium tuberculosis (MTB), remains one of the most prevalent and deadly infectious diseases worldwide.Currently, there are complex interactions between host cells and pathogens in TB. The onset, progression, and regression of TB are correlated not only with the virulence of MTB but also with the immunity of TB patients. Exosomes are cell-secreted membranebound nanovesicles with lipid bilayers that contain a variety of biomolecules, such as metabolites, lipids, proteins, and nucleic acids. Exosome-mediated cell-cell communication and interactions with the microenvironment represent crucial mechanisms through which exosomes exert their functional effects. Exosomes harbor a wide range of regulatory roles in physiological and pathological conditions, including MTB infection. Exosomes can regulate the immune response, metabolism, and cellular death to remodel the progression of MTB infection. During MTB infection, exosomes display distinctive profiles and quantities that may act as diagnostic biomarkers, suggesting that exosomes provide a revealing glimpse into the evolving landscape of MTB infections. Furthermore, exosomes derived from MTB and mesenchymal stem cells can be harnessed as vaccine platforms and drug delivery vehicles for the precise targeting and treatment of TB.In this review, we highlight the functions and mechanisms through which exosomes influence the progression of TB. Additionally, we unravel the critical significance of exosomal constituents in the diagnosis and therapeutic applications of TB, aiming to offer novel perspectives and strategies for combating TB.